2020
DOI: 10.1101/2020.07.07.20147975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accuracy of online symptom checkers and the potential impact on service utilisation

Abstract: Objectives: The aims of this study are firstly to investigate the diagnostic and triage performance of symptom checkers, secondly to assess their potential impact on healthcare utilisation and thirdly to investigate for variation in performance between systems. Setting: Publicly available symptom checkers Participants: Publicly available symptom-checkers were identified. A standardised set of 50 clinical vignettes was developed and systematically run through each system by a non-clinical … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…The finding of this study, namely that the Ada app has relatively high accuracy with regard to condition suggestion and urgency compared with other available SAAs, reflects the findings of other studies (Nateqi et al 2019;Ceney et al 2020;Gilbert et al 2020). The Ada app was recently compared with general practitioners (GPs) and competitor apps in a 200-vignette study (Gilbert et al 2020).…”
Section: Comparisons With the Wider Literature On The Performance Of Symptom Assessment Appssupporting
confidence: 78%
“…The finding of this study, namely that the Ada app has relatively high accuracy with regard to condition suggestion and urgency compared with other available SAAs, reflects the findings of other studies (Nateqi et al 2019;Ceney et al 2020;Gilbert et al 2020). The Ada app was recently compared with general practitioners (GPs) and competitor apps in a 200-vignette study (Gilbert et al 2020).…”
Section: Comparisons With the Wider Literature On The Performance Of Symptom Assessment Appssupporting
confidence: 78%
“…Building on prior related work [12, 22, 27, 36, 52, 53], we adopted a clinical vignette approach to measure the performance of Avey alongside several other checkers. A seminal work at Harvard Medical School has established the value of this approach [22, 52, 53] for testing checkers, especially that it has been also a common method to test physicians on their diagnosis abilities [53].…”
Section: Methodsmentioning
confidence: 99%
“…They also observed that AI-based checkers outperform rule-based ones (i.e., checkers that do not use AI). Akin to Hill et al [27], Ceney et al [12] detected a significant variation in accuracy across 12 checkers, ranging from 22.2% (CAIDR [11]) to 72% (Ada) using 𝑀5.…”
Section: Comparison To the Wider Literaturementioning
confidence: 99%
See 2 more Smart Citations